2014
DOI: 10.1136/jnnp-2014-309571
|View full text |Cite
|
Sign up to set email alerts
|

Interictal cerebral and systemic endothelial dysfunction in patients with migraine: a case–control study

Abstract: BackgroundAlthough systemic endothelial function is unimpaired in migraine, it is unknown whether cerebral endothelial function impairment exists in migraineurs.Materials and methodsWe conducted a prospective study to assess endothelial function in migraineurs (n=45) and healthy volunteers (n=44). Cerebral endothelial function was assessed by Breath Holding Index (BHI) on transcranial Doppler in bilateral middle cerebral artery (MCA at 30–60 mm), posterior cerebral artery (PCA at 60–80 mm) and basilar artery (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 27 publications
2
31
1
2
Order By: Relevance
“…Inflammatory cytokines released in the aura phase activate the endothelium leading to procoagulatory and prothrombotic state [55]. However, research of cerebrovascular reactivity in migraineurs has demonstrated conflicting data (decreased or increased cerebral vascular reactivity) in regard to the causal relationship of endothelium dysfunction in stroke pathogenesis [6062]. …”
Section: The Underlying Mechanisms Of Coincidence Migraine and Strokementioning
confidence: 99%
“…Inflammatory cytokines released in the aura phase activate the endothelium leading to procoagulatory and prothrombotic state [55]. However, research of cerebrovascular reactivity in migraineurs has demonstrated conflicting data (decreased or increased cerebral vascular reactivity) in regard to the causal relationship of endothelium dysfunction in stroke pathogenesis [6062]. …”
Section: The Underlying Mechanisms Of Coincidence Migraine and Strokementioning
confidence: 99%
“…Systemic endothelial dysfunction has been widely tested in migraine with forearm blood flow by venous plethysmography, flow-mediated dilatation, and pulse-wave velocity analyses, yielding conflicting results [ 48 - 53 ]. In contrast, cerebral vascular reactivity has been consistently reported to be decreased in migraine, especially in the posterior circulation [ 51 , 52 ]. It seems that there is a lack of association between systemic and cerebral endothelial dysfunction in migraine [ 54 ].…”
Section: Migraine As a Risk Factor For Cerebral Infarction (Migraine-mentioning
confidence: 99%
“…The pathophysiology of CoA involves more than simple mechanical obstruction of the aorta. There may exist more complexity such as impairment of systemic endothelial function, which may be associated with migraine pathophysiology . It is reported that abrupt hypotension precipitates migraine attacks with aura .…”
Section: Discussionmentioning
confidence: 99%